C14H10 polycyclic aromatic hydrocarbon formation by acetylene addition to naphthalenyl radicals observed. Issue 26 (24th June 2021) - Yang, Jeehyun; Smith, Mica C.; Prendergast, Matthew B.; Chu, Te-Chun; Green, William H.
Abstract : Primary reaction pathways for 2-naphthalenyl + acetylene predicted by the kinetic model under the experimental conditions in this work. Abstract : The formation of polycyclic aromatic hydrocarbons (PAHs) during combustion has a substantial impact on environmental pollution and public health. The hydrogen-abstraction-acetylene-addition (HACA) mechanism is expected to be a significant source of larger PAHs containing more than two rings. In this study, the reactions of 1-naphthalenyl and 2-naphthalenyl radicals with acetylene (C2 H2 ) are investigated using VUV photoionization time-of-flight mass spectrometry at 500 to 800 K, 15 to 50 torr, and reaction times up to 10 ms. Our experimental conditions allow us to probe the Bittner–Howard and modified Frenklach HACA routes, but not routes that require multiple radicals to drive the chemistry. The kinetic measurements are compared to a temperature-dependent kinetic model constructed using quantum chemistry calculations and accounting for chemical-activation and fall-off effects. We measure significant quantities of C14 H10 (likely phenanthrene and anthracene), as well as 2-ethynylnaphthalene (C12 H8 ), from the reaction of the 2-naphthalenyl radical with C2 H2 ; these results are consistent with the predictions of the kinetic model and the HACA mechanism, but contradict a previous experimental study that indicated no C14 H10 formation in the 2-naphthalenyl + C2 H2 reaction. In the 1-naphthalenyl radical + C2 H2 reaction system, the primary product measured is C12 H8, consistent with the predicted formation of acenaphthylene via HACA. The present work provides direct experimental evidence that single-radical HACA can be an important mechanism for the formation of PAHs larger than naphthalene, validating a common assumption in combustion models.